Grey and harbor seals in France (mainland and Saint-Pierre et Miquelon): microbial communities and identification of a microbial source tracking seal marker - Godino Sanchez, Alisson; Serghine, Joëlle; Le Mennec, Cécile; Noël, Cyril; Schaeffer, Julien; Goraguer, Herlé; Vincent, Cécile; Vitré, Thomas; Le Guyader, Françoise S.; Gourmelon, Michèle (Frontiers in Microbiology, 2024)
IntroductionSeals, protected wild marine mammals, are widely found in waters around the world. However, rising concerns about their increasing numbers in some areas have led to potential worries regarding microbiological contamination of coastal areas by their feces, which could impact bathing and shellfish-harvesting activities. To the best of our knowledge, no study has been conducted on the bacterial and RNA viral communities present in the feces of both grey and harbor seals, which are the two main seal species observed in mainland France and overseas.MethodsFecal bacterial (n = 132) and RNA viral (n = 40) communities of seals were analyzed using 16S rRNA gene amplicon high-throughput sequencing and viral RNA sequencing methods, respectively. In addition, to identify the specific characteristics of seal fecal microbial communities compared to other animal fecal microbial communities that may also contaminate coastal areas, the bacterial communities of seals were compared to those of wild waterbirds and breeding animals (i.e., cattle and pigs) which could be present in upstream catchments of coastal areas. Finally, ANCOM was used to identify unique and seal-associated Amplicon Sequence Variants (ASVs), aiming to develop a Microbial Source Tracking (MST) bacterial qPCR marker associated with seals.Results and discussionThe bacterial communities of grey and harbor seals were not found to be significantly different and were characterized by a predominance of Firmicutes, including the genera Clostridium sensu stricto 1 and Peptoclostridium, followed by Fusobacteriota with the genus Fusobacterium, and Bacteroidota with the genus Bacteroides. However, variations in bacterial communities between sites and individuals were observed. Similar observations were made for the RNA viral communities being characterized by a predominance of Picobirnaviridae (44% of total reads) and Astroviridae (15%). This study successfully developed a sensitive (89.8%) and specific (97.1%) MST qPCR marker targeting grey seal-associated bacteria belonging to the Bifidobacteriaceae family. This marker can be used to identify potential fecal contamination of coastal areas by seals and complements the MST toolboxes of markers already developed for humans, wild birds and livestock.